Air Quality and Human Health Risk Assessment in the Residential Areas at the Proximity of the Nkolfoulou Landfill in Yaoundé Metropolis, Cameroon - Gilbert Feuyit; Serge Nzali; John Ngolui Lambi; Samuel Laminsi (Journal of Chemistry)
Landfill operations generate particulate matters (PM) and toxic gases that can jeopardize human health. This study was conducted in February 2016 to assess the air quality in the residential areas around the Nkolfoulou landfill in Yaoundé. The concentrations of PM2.5 and PM10 were determined with Dust Sentry while those of CO, O3, NO2, CH4, CO2, CH2O, H2S, and SO2 were measured using gas sensors. At the landfill neighborhood, 30% of the daily mean concentrations of PM2.5 and PM10 crossed the daily safe limits. The concentrations of CO, O3, NO2, SO2, and H2S recorded at the propinquity of the landfill complied with the emission standards. Near the landfill, hourly mean concentrations of CH2O and H2S higher than their odour thresholds were recorded at each sampling site. The concentrations of CH4 were less than its lower explosive limit while those of CO2 were far below the safe limit for occupational health. The values of cancer risk (CR) due to the inhalation of CH2O were >10−6 while those of hazard index (HI) due to the inhalation of CH2O, H2S, and SO2 were <1. Thus, there might be increased cancer risks at the Nkolfoulou landfill neighborhood, whereas the increased non-cancer risks were low. 96.76% of the daily average levels of air pollutants registered near the landfill surpassed those recorded at the remote control site. Hence, the landfill operations might be supplying air pollutants to the neighbouring residential areas.